Radical thoracoplasty using osseous osteosyn thesis in chest deformity in patients with Currarino–Silverman syndrome - A. N. Lednev; A. A. Pechetov; I. I. Danilov; N. V. Gulova (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. Currarino – Silverman syndrome is a very rare deformity of the sternum and chest wall resulting from premature obliteration of the manubriosternal joint. In this paper, we present the experience of radical thoracoplasty using osseous osteosynthesis in patients with Currarino – Silverman syndrome.METHODS AND MATERIALS. Surgical treatment includes bilateral subcostal resection of rib cartilage, osteotomy of the sternum and its correction in the correct anatomical position using intraosseous and osseous osteosynthesis.RESULTS. The study included 4 patients (1 men and 3 women) aged from 22 to 30 years. The average surgery time was 146±17 minutes. Patients were activated on the 2nd day and discharged on the 7th day after surgery. The observation period after correction ranged from 6 months to 3 years. No complications or relapses were recorded. All patients are satisfied with the results of the correction.CONCLUSIONS. Radical thoracoplasty using osseous osteosynthesis for chest deformity in patients with Currarino – Sil verman syndrome allows achieving an optimal correction result with minimal postoperative scarring and high satisfaction.